Exploring Authentic Learning Strategies In A Mobile Cloud Computing Environment (AuLStra) Among Primary School English Language Learners’ Writing Experience - Bun Tiang, Chin Da (2022)
This study explores how primary school English language learners in a Chinese national-type primary school in Malaysia used Authentic Learning Strategies in a mobile cloud computing environment (AuLStra) to write in English. This thesis continues and develops within a situated learning theory framework by investigating the primary schoolchildren’s experiences of AuLStra through the lens of socio-cultural theory, and exploring how co-constructed knowledge is utilised in online collaborative writing tasks. Drawing upon case study design, this study aims to provide some insights on online collaborative writing from the participants’ perspectives. It illustrates how writing is co-authored, elucidates aspects that impact the potential of integrating AuLStra in English writing classroom, and explores how the primary school English language learners used AuLStra to overcome writing apprehension. The primary school English language learners took part in a series of English language lessons on Google Meet, during which they were video-recorded using Meet recording function, as they collaboratively performed the authentic writing tasks. Besides taking part in AuLStra Writing Class, the primary school English language learners and their English language teacher kept reflective e-journals (Teacher eJournal and My eDiary). On the other hand, through the use of interviews, five teachers from the same school identified roles of AuLStra in English writing.